Analysis of Emissions and Environmental Impacts of the Production and Distribution Process of Two Aspect Traffic Lights Using the Life Cycle Assessment Method - Dini Yekti; Farida Pulansari; Nur Rahmawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In Indonesia, carbon emissions declarations are still voluntary and their implementation by the business world is still rare. This study analyzes the potential environmental impacts and large emissions resulting from the supply chain traffic light (production and distribution) of traffic lights in two aspects at company in Sidoarjo. This study is relevant to the urgency of the Sustainable Development Goals (SDGs) number 13, Climate Action. Which emphasizes climate change mitigation and environmentally friendly industrial innovation. Traffic light production and distribution were chosen because of their significant contribution to the company's operations, long production cycles, and high energy consumption. Life Cycle Assessment (LCA) was applied to evaluate carbon dioxide emissions and environmental impacts at each process stage. The results showed that the processing and maintenance sub-production had the highest environmental impact, so process optimization was needed. The largest impact in the production cycle was human toxicity water with a value of 4.51. To reduce environmental effects, it is recommended to apply environmentally friendly technologies and optimize raw materials, such as the use of aluminum scrap and water recovery systems. These findings are expected to contribute to emission mitigation strategies and the formulation of sustainable policies for the traffic light manufacturing industry.